The diagnostic potential of extracellular vesicles in virus-related diseases - Qing Gao; Qing Gao; Yuqing Zhan; Yuqing Zhan; Jianhao Zhang; Jianhao Zhang; Dongyu Sun; Dongyu Sun; Huayuan Xiang; Huayuan Xiang; Chenxuan Bao; Chenxuan Bao; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
Extracellular vesicles (EVs), a heterogeneous population of lipid bilayer-enclosed membranous particles, are widely involved in cell-cell communication and pathophysiological regulation. Recent advances reveal their dual functionality in viral pathogenesis: while facilitating viral dissemination through transport of pathogenic components, they simultaneously orchestrate host antiviral defense mechanisms. The unique molecular cargo loading capacity and high stability of EVs in body fluids make them ideal biomarkers for early infection diagnosis, treatment monitoring, and prognostic evaluation of virus-related disease. Compared to traditional viral detection methods, EV-based liquid biopsy techniques exhibit distinct advantages, including non-invasiveness and enhanced sensitivity thresholds. This review systematically examines the diagnostic potential of EV biomarkers in viral infections, offering novel perspectives for developing precision diagnostics and therapeutic interventions.